Bio-inspired synthesis of xishacorenes A, B, and C, and a new congener from fuscol. Issue 33 (10th July 2019) - Rovira, Alexander R.; Müller, Nicolas; Deng, Weiwen; Ndubaku, Chudi; Sarpong, Richmond
Abstract : In this manuscript, we describe the conversion of fuscol, a natural product isolated in 1978, to xishacorenes A, B, and C, isolated in 2017, as well as a previously unreported congener, which we have named xishacorene D. Abstract : The xishacorene natural products are structurally unique apolar diterpenoids that feature a bicyclo[3.3.1] framework. These secondary metabolites likely arise from the well-studied, structurally related diterpenoid fuscol. In this manuscript, we describe the conversion of fuscol to xishacorenes A, B, and C, as well as a previously unreported congener, which we have named xishacorene D. In addition, we describe immunomodulatory activity studies of the xishacorenes, a structurally related analogue, and fuscol. These studies were aided by an accurate determination of the physical properties ( e.g., molar extinction coefficient) of the highly apolar xishacorenes.